Liberdade assistida em Belo Horizonte : a medida de ouro na ressocialização do adolescente em conflito com a lei? - Héllen Matos Pereira (2023)
This research aims to verify if the juvenile delinquency program of Probation in Belo Horizonte/MG can positively transform the life of the teenager subjected to it and, mainly, prevent him from remaining in crime. Its preparation consisted of two types of investigation: quantitative and qualitative. The first stage was carried out by consulting 197 lawsuits referring to adolescents who were imposed the program of Probation in 2019 in Belo Horizonte, available at the Childhood and Youth Court. Based on the reading guided by a structured form, a profile of this teenager was drawn up in relation to gender, age, education, race, family composition, work, infraction committed, time of its occurrence and others, in addition to verifying the commitment of new offense or crime. The qualitative stage consisted of carrying out semi-structured interviews with probation officers and adolescents who are submitted to Probation in Belo Horizonte, about their view on the program and on the life changes observed. The aim of this research was to evaluate whether the main objective of resocialization and overcoming the cycle of criminality was successfully achieved, thus achieving the right to full protection of adolescents enshrined in law n. 8,069/1990. The quantitative and qualitative results showed a higher recidivism rate than that observed in studies of juvenile detention, but there are positive changes in the lives of adolescents that are a result of Probation. The study therefore sought to contribute to the improvement of the measure, by pointing out its positive aspects and its current challenges.